How to do business with lysosomes: Salmonella leads the way. (February 2019) - Tuli, Amit; Sharma, Mahak
Abstract : Pathogens have devised various strategies to alter the host endomembrane system towards building their replicative niche. This is aptly illustrated by Salmonella Typhimurium, whereby it remodels the host endolysosomal system to form a unique niche, also known as Salmonella -containing vacuole (SCV). Decades of research using in vitro cell-based infection studies have revealed intricate details of how Salmonella effectors target endocytic trafficking machinery of the host cell to acquire membrane and nutrients for bacterial replication. Unexpectedly, Salmonella requires host factors involved in endosome-lysosome fusion for its intravacuolar replication. Understanding how Salmonella obtains selective content from lysosomes, that is nutrients, but not active hydrolases, needs further exploration. Recent studies have described heterogeneity in the composition and pH of lysosomes, which will be highly relevant to explore, not only in the context of Salmonella infection, but also for other intracellular pathogens that interact with the endolysosomal pathway.